(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
The concept of disability has undergone a profound theoretical and regulatory evolution, shifting from a medical paradigm to a bio-psycho-social model. The modern approach defines disability not as a mere individual condition, but as the result of interactions between functional limitations, environmental factors, and social barriers. Law No. 62/2024 enshrines this innovative vision within the Italian legal framework, introducing assessment criteria based on a multidimensional evaluation aimed at providing personalized support for persons with disabilities. This paper critically analyzes the new assessment process established by Law No. 62/2024, evaluating its effectiveness, consistency with the new paradigm, and practical implementation in real-world contexts. It demonstrates that the approach introduced by Law 62/2024 represents a significant advancement in the definition and assessment of disability in Italy: it shifts the focus from merely verifying functional limitations to building life projects truly centered on the individual.